Table of contents and introductory materials for Vl. 19, no.2, Fall 2011 - Bruce Quantic (The Advocate, 2011)
This content includes the table of contents and editorial information, a message from president of ATE-E, and a message from the editor for vol. 19, no.2 (Fall 2011) for The Advocate.